Guidelines for maternal and neonatal “point of care”: needs of and attitudes towards a computerized clinical decision support system in rural Burkina Faso - Zakane, Alphonse; Gustafsson, Lars L; Tomson, Göran; Loukanova, Svetla; Sié, Ali; Nasiell, Josefine; Bastholm-Rahmner, Pia (International journal of medical informatics, 2014)
Background - In 2010, 245,000 women died due to pregnancy-related causes in sub-Saharan Africa and southern Asia. Our study is nested into the QUALMAT project and seeks to improve the quality of maternal care services through the introduction of a computerized clinical decision support system (CDSS) to help healthcare workers in rural areas. Healthcare information technology applications in low-income countries may improve healthcare provision but recent studies demonstrate unintended consequences with underuse or resistance to CDSS and that the fit between the system and the clinical needs does present challenges. - Aims - To explore and describe perceived needs and attitudes among healthcare workers to access WHO guidelines using CDSS in maternal and neonatal care in rural Burkina Faso. - Methods - Data were collected with semi-structured interviews in two rural districts in Burkina Faso with 45 informants. Descriptive statistics were used for the analysis of the quantitative part of the interview corresponding to informants’ background. Qualitative data were analyzed using manifest content analysis. - Results - Four main findings emerged: (a) an appreciable willingness among healthcare workers for and a great interest to adapt and use modern technologies like computers to learn more in the workplace, (b) a positive attitude to easy access of guidelines and implementation of decision-support using computers in the workplace, (c) a fear that the CDSS would require more working time and lead to double-work, and (d) that the CDSS is complicated and requires substantial computer training and extensive instructions to fully implement. - Conclusions - The findings can be divided into aspects of motivators and barriers in relation to how the CDSS is perceived and to be used. These aspects are closely connected to each other as the motivating aspects can easily be turned into barriers if not taken care of properly in the final design, during implementation and maintenance of the CDSS at point of care.